Dampak Penerapan Nilai Kearifan Lokal Sarapatanguna terhadap Etika Aparatur Sipil Negara pada Pemerintah Kota Baubau - La Asiri; Junaid Gazalin (Departement of Mathematics Education, 2023)
This study aims to explore the value of local wisdom of Sarapatangunake in the implementation of government, especially in the ethics of public servants.how the impact caused by implementing these values. The type of research used is descriptive research with a qualitative approach. Data collection techniques are Observation, Interview, Documentation and Literature Studies. Techniques Data analysis in research is data reduction, data presentation, and drawing conclusions. The results obtained in the research are to have a positive impact with the value of Sarapatanguna Wisdom (Pomaamasiaka; PopiapiaraPomaemaeya and Poangka-angkataka) are philosophical values embedded in cultural values that are full of meanings in the life of the Buton people that teach the importance of moral values that are applied to the implementation of government mainly in public servicescan foster mental attitudes, good morals so that the implementation of Government Ethics can improve the achievement of organizational performance is reflected in the attitude of government officials, especially in good and correct behavior in accordance with the values of primacy related to the nature, dignity, and dignity, problems of decency and decency reflected in the behavior of officials.